The Relationship of Physical Activities and Student Learning Outcomes of Physical Education - Tri Irianto; Ramadhan Arifin; Muhammad Firmansyah (UNIB Press, 2021)
The purpose of this study was to determine the relationship between physical activity and learning outcomes of sports physical education and the health of students at SMA Negeri 1 Banjarbaru. The method used in this research is a survey method. The population in this study was taken from male and female students at the State Senior High School 1 Banjarbaru aged 16-19 years, the population in the XI grade of the State Senior High School 1 Banjarbaru as many as 231 students. In comparison, the research sample was 184 students with the cluster sampling technique.The results of the research on the physical activity of students of SMA Negeri 1 Banjarbaru found that the classification of